Implementation of Technical-Vocational Education and Training at German-Malaysian Institute, Malaysia - Hanafi, Ivan (2007)
Technical Education and Vocational Training (TEVT) system has an important role in providing high skilled labour to fulfil the needs of industry. However, most of the existing graduates of TEVT system have not yet attained the standard of job quality desired by the industry. In fact, the industry is less satisfied with the achievement of TEVT graduates, both in the technical and personal perspectives. Therefore an in-depth research of TEVT system is necessary to identify effective TEVT system that can successfully equip students with the technical skills and able to fulfil the current work demands and professional expectations. The main objective of this research was to study the implementation of TEVT system in the German-Malaysian Institute (GMI) which has been successful in preparing graduates for middle level job tasks. In addition, the study also seeked to analyse the organizational system, teaching and learning strategy employed, the curriculum, industrial involvement, and students’ employability skills of the institute. The study utilized qualitative method to gain information pertaining to the implementation of the TEVT system in the GMI. To obtain a clearer picture of students’ employability skills, quantitative method was employed. Therefore, the researcher used the mixed-method research design in the conduct of the study. The organization of TEVT system of the GMI which is in the form of a company with limited guarantee is a joint venture project between the Governments of Malaysia and Germany. The GMI as a centre for advanced technology, and technical-vocational teacher education, provides consultancy and technical services to local industry. In fact, the GMI is an integrated TEVT system with strength in the technical field, education and training, and industrial relation. The study has found six approaches and strategies of teaching and learning used in the GMI. These were adjustments of dynamic curriculum, broad-based learning, hands-on training approach, student-centred learning, project-based learning, and control in-plant training program. Most of the strategies practiced were inclined towards the inclusion of the Theory of Constructivism. The study also discovered three dominant factors that encouraged students’ enthusiasm and spirits to learn. The factors were availability of learning facilities, instructors’ competence and experiences, and learning management. Students’ employability skills were also measured. It was found that the mean score for overall employability skills was slightly high. Whereas, the mean score for personal quality was the highest among all the aspects of the employability skill’s variable. In conclusion, the organizational system employed, teaching and learning strategies, and the three dominant input factors (availability of learning facilities, instructors’ competence and experiences, and learning management) had important influence in the implementation of an effective TEVT system. The above components also provided valuable contribution in providing technical and employability skills in the preparation of students for working life. The researcher conceptualized the findings of the study into a model of technical education and vocational training system for the German-Malaysian Institute.